IMPLEMENTATION OF PSAK 71 AND FINANCIAL STATEMENT QUALITY IN INDONESIAN BANKING INDUSTRY - Indriani, Eni; Inapty, Biana Adha; Waskito, Iman (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
The implementation of PSAK 71 requires the companies to have a greater allowance for impairment losses (CKPN) than the previous standard. This is an opportunity for companies to maintain the elements of management in such a way. Managers' opportunistic behavior in exploiting opportunities will affect the financial statement quality because they are assumed to contain earnings management. It is feared that an increase in CKPN determined by corporations will have an impact on the financial statement quality. This research aims to determine the impact of implementing PSAK 71 on the financial statement quality in Indonesian banking industry. The sample consist of 41 companies listed on the Indonesia Stock Exchange for the 2019–2020 period. Based on the results of data processing with the use of Eviews version 12, it can be concluded that the implementation of PSAK 71 has a positive effect on financial statement quality in Indonesian banking industry. The results of this research contribute to the study of the the new PSAK implementation and as an evaluation for the standard-setter board